Z‐Scheme 2D/2D Heterojunction of CsPbBr3/Bi2WO6 for Improved Photocatalytic CO2 Reduction. (11th September 2020) - Jiang, Yong; Chen, Hong‐Yan; Li, Jun‐Yan; Liao, Jin‐Feng; Zhang, Hong‐Hong; Wang, Xu‐Dong; Kuang, Dai‐Bin
Abstract: Heterojunction engineering, especially 2D/2D heterojunctions, is regarded as a quite promising strategy to manipulate the photocatalytic performance of semiconductor catalysts. In this manuscript, a direct Z‐scheme 2D/2D heterojunction of CsPbBr3 /Bi2 WO6 is designed and fabricated by a simple electrostatic self‐assembly process. By using ultrathin nanosheets with several atomic layers as the building blocks, a close CsPbBr3 /Bi2 WO6 heterointerface over large area with quite a short charge transport distance is obtained, which enables a valid Z‐scheme interfacial charge transfer between Bi2 WO6 and CsPbBr3 and thus boosts charge separation. The CsPbBr3 /Bi2 WO6 heterojunction exhibits a superior photocatalytic performance toward CO2 reduction. By incorporating Pt nanoparticles as the cocatalyst, a high photoelectron consumption rate of 324.0 µmol g −1 h −1 under AM 1.5G irradiation (150 mW cm −2 ) is obtained, which is 12.2 fold higher than that of CsPbBr3 nanosheets. Moreover, a stable product yield of up to 1582.0 µ mol g −1 and electron consumption yield of 8603.0 µ mol g −1 for photocatalytic CO2 reduction to CO (11.4%) and CH4 (84.3%) can be achieved after 30 h of continuous catalytic reaction. The accelerated photogenerated charge transfer and spatial charge separation are investigated in detail by ultrafast spectra, photoelectrochemical test, and Kelvin probe force microscopy. Abstract : A Z‐Scheme 2D/2D heterojunction of CsPbBr3 /Bi2 WO6 is fabricated using a simple electrostatic assembly process. The as‐formed heterojunction possesses a large interface contact area and quite a short charge transport distance, which enable efficient Z‐scheme charge transfer and separation between Bi2 WO6 and CsPbBr3, as well as remarkably enhanced performance toward photocatalytic CO2 reduction.